A value-theoretic approach to economic dynamics and evolution—synthesizing different Marxian modules in a simulation model - Frank Beckenbach (Review of Evolutionary Political Economy, 2020)
This part is devoted to simulation experiments based on the simulation model developed in part I from the value-theoretic reconstruction of the main parts of Marx's critique of Political Economy. After introducing the main parameters and the range of their variation (Section 1), a singular run as well as a sensitivity analysis for the chosen standard configuration (`moderation regime') is presented in Section 2. This is accomplished by configurations depicting characteristics of the capitalist development emphasized by Marx, i.e. the social conflict regime (Section 3) and the crisis regime (Section 4). Finally, an assessment of the simulation results (Section 4) is given, and conclusions as well as research requirements are discussed (Section 5).
Keywords: B14; B15; B51; B52; C63; E11; P10; 320; Marx; Theory of value; Evolution; Social exploitation; Class antagonism; Accumulation; Reproduction; Profit rate; Crisis; Simulation